Rafflesia banaoana (Rafflesiaceae) another new species from Luzon, Philippines - Malabrigo, Pastor L., Jr (Asia Life Sciences : the Asian International Journal of Life Sciences, 2010)
Rafflesia banaoana Malabrigo, a new species from Kalinga Province, Northern Luzon, Philippines is described. It is tenth endemic Rafflesia species thus far described from the Philippines, and the sixth reported from Luzon Island. Its size comparable to other Philippine species, namely: Rafflesia mira Fernando & Ong and R. speciosa Barcelona & Fernando. Perigone color and wart ornamentations closely resemble R. baletei Barcelona & Cajano but the species differs in size and in the number, structure and arrangement of processes on the disk.